Evaluation of hybrid solar - Biomass dryer with no load - Yassen, T.A. (EDP Sciences, 2014)
Experimental study was carried out to investigate the performance of designed and fabricated hybrid solar-biomass dryer without load. The solar side was a natural convection mixed mode, while the biomass side was a hot air produced from a burner/gas to gas heat exchanger. The experiments have been conducted to test the dryer temperature, inlet and outlet relative humidity, outlet velocity, and biomass feeding rate. In the solar mode the maximum dryer temperature was 63°C. Behaviours of the velocity in the dryer was found to follow solar radiation available to the dryer. The velocity was in the range of 0.6 - 1.35 m/s through the 0.0176 m2 area of the outlet when the solar radiation was in the range of 150 - 880 W/m2. Two feeding rates of wood were used to investigate the dryer performance through the night. The results showed that at feeding rate 278 g/hr, the drying air mean temperature was 62°C. This temperature was more suitable than the measured drying air temperature at feeding rate 490 g/hr. Also the 62 °C drying environment is more stable and feasible for drying almost all types of products. © 2014 Owned by the authors, published by EDP Sciences.